Risk Factors and Prognostic Follow-Up of Vasovagal Syncope Children With Seizure-Like Activities During Head-Up Tilt Test Induced-Syncope - Zou, Runmei; Wang, Shuo; Wen, Wen; Cai, Hong; Wang, Yuwen; Liu, Ping; Li, Fang; Lin, Ping; Wang, Cheng (Frontiers in Cardiovascular Medicine, 2022)
Objectives：Seizure-like activities during head-up tilt test (HUTT) are common in adults with vasovagal syncope (VVS), which have not been elaborated in pediatric patients. This study aimed to investigate the clinical characteristics and hemodynamic parameters of pediatric VVS patients with seizure-like activities during HUTT-induced syncope and assess the prognosis of these patients through a follow-up. Methods：VVS children with or without seizure-like activities during HUTT-induced syncope were included in convulsive group or non-convulsive group. The clinical characteristics and hemodynamic parameters during HUTT-induced syncope were retrospectively reviewed from the HUTT case report form and analyzed. Data of follow-up were collected by HUTT case report form or telephone. Results：VVS children with seizure-like activities during HUTT-induced syncope had a higher proportion of mixed or cardioinhibitory responses to HUTT (61.8% vs. 35.4%, P=0.002; 27.9% vs. 3.1%, P＜0.001, respectively), a lower heart rate (median 47 bpm vs. 77 bpm, P＜0.001) and a higher ratio of asystole (39.7% vs. 1.5%, P＜0.001) at the time of syncope compared with non-convulsive group. No significant difference was exhibited in negative HUTT conversion rate and the proportion of re-syncope patients between convulsive and non-convulsive groups at follow-up (both P＞0.05). None of these convulsive patients underwent pacemaker implantation during follow-up. Conclusions：Pediatric VVS patients with seizure-like activities during HUTT-induced syncope had severe transient hemodynamic parameter changes with decreased heart rate and more occurrence of asystole at the time of syncope. However, these patients did not have a poor prognosis at follow-up.